Implementation of modified chaos embedded symbiotic organisms search algorithm to solve economic dispatch problem / Mohamad Khairuzzaman Mohamad Zamani ...[et al.] - Mohamad Zamani, Mohamad Khairuzzaman; Musirin, Ismail; Suliman, Saiful Izwan; Bouktir, Tarek; Kalam, Akhtar (UiTM Press, 2018)
With the increase in fossil fuel prices, power system operators were facing a challenge to reduce the operational cost since it is directly related to the consumer electricity price. To counter the issue, the optimal power output of generation units were obtained by solving economic dispatch problem. In past years, various researchers have attempted to solve the problem using different optimization technique. However, several optimization techniques failed to produce a high-quality solution due to the drawbacks of the optimization process. This paper presents a new optimization technique termed as modified chaos embedded symbiotic organisms search technique in the attempt to produce a higher quality solution. The proposed technique was employed to solve economic dispatch problem on a 26-bus IEEE reliability test system (RTS) at several case studies. Comparative studies with respect to PSO, EP and AIS has yielded that the proposed algorithm has proven its superiority over the other optimization technique.